A Case Report: Serial Case of Spontaneous Pneumomediastinum and Subcutaneous Emphysema in COVID-19 Patients - Faradilla Novita Anggreini; Putu Utami Dewi; Firman Parulian Sitanggang; Dewa Gde Mahiswara Suadiatmika (Indonesian Journal of Global Health Research, 2025)
Coronaviruses are pathogens that affect both humans and animals and play a significant role in one of the most persistent disease outbreaks to date, known as Coronavirus Infectious Disease 2019 (COVID-19). The COVID-19 pandemic, declared by the World Health Organization (WHO) in March 2020, was classified as a global public health emergency due to its continued transmission, widespread impact, and the emergence of various viral variants. Before the development of vaccines, at the early stage of the pandemic, there were 5,596,550 confirmed COVID-19 cases worldwide, with a mortality rate of 353,373 cases. This study present Serial Case of Spontaneous Pneumomediastinum and Subcutaneous Emphysema in COVID-19 Patients. This study was a case report that describing detailed account of a patient's diagnosis, treatment, and follow-up a rare case. A critical review of the case report was conducted to assess the validity and reliability of the findings and to identify any limitations of the study. We present a serail case of Spontaneous Pneumomediastinum and Subcutaneous Emphysema in COVID-19. Various case reports and studies have shown that subcutaneous emphysema and pneumomediastinum can occur in COVID-19 patients both with and without mechanical ventilation (spontaneously). Extensive subcutaneous emphysema causing airway compression is an extremely rare manifestation of COVID-19 infection. Subcutaneous emphysema and pneumomediastinum are uncommon conditions associated with COVID-19 and can indicate a poor prognosis, leading to increased morbidity and prolonged hospitalization. Pneumomediastinum, pneumothorax, and subcutaneous emphysema may arise as complications of COVID-19 itself or as consequences of its management, such as mechanical ventilation or other iatrogenic interventions.